The post-1994 land reform prism to interrogate development planning in South Africa - Molokwane, Masibane John (University of the Witwatersrand, Johannesburg, 2024)
The Republic of South Africa’s post-1994 government has embarked on developing numerous policies, legislations, and in 2011, a National Development Plan to advance its economic development trajectory. Yet, despite the various policies, plans and legislations, unmanageable levels of poverty, inequality, and unemployment continue to persist and, in certain areas, increased. The post-1994 government, in line with developed policies and legislations, has sought to utilise re-industrialisation, manufacturing, small business development, mining, and other such economic drivers. While land reform has featured in various policies post-1994, it has not been elevated and used as a central means in advancing development planning and development to address socio-economic challenges. This study, therefore, took a unique approach, unlike previous studies examining land reform in the context of development planning and development. The study’s unique approach was informed by the instrumentality of land reform in advancing development planning and catalysing industrialisation in selected Asian States. This study aimed to address the dearth of literature that prioritises and focuses on the instrumentality of land in development and the inability of the post-1994 South African land reform approach to view land as a development tool. An interpretive sequential mixed qualitative methods study was employed to theorise how development planning can be modelled to feature a re-shaped and re-planned land reform in a development plan. The result of this approach was to present a nuanced contribution to knowledge in the field of development planning, namely a framework that elevates land reform as a central means of development for South Africa’s problematic re-industrialisation.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; development planning; planning practice; planning theory; development; land; land reform; Asian land reform; SDG-15: Life on land